Power System Stability Assessment for Karnali Province of Nepal - Shrestha, Navaraj; Maharjan, Shreeshuva; Bista, Aayush; Gurung, Samundra; Bala, Sadam; Bista, Diwakar (Journal of Science and Engineering, 2025)
Karnali province in Nepal faces significant challenges in ensuring a stable and reliable power supply due to its weak transmission network, high system losses, and limited local generation capacity. Therefore, there is a high need for the assessment of the performance and power system stability of the current Karnali grid to mitigate any potential issues that can occur due to the addition of load. This paper conducts a comprehensive assessment of the existing Karnali province power grid to identify major performance bottlenecks and stability issues, covering voltage, angle (transient and small signal), and frequency stability, which were performed under four operational scenarios: base case, increased load, reduced load, and N-1 contingency. Results indicate the significant voltage drop and low voltage stability margins in multiple substations, especially in Khalanga, Manma, and Kudu substations. Modal analysis revealed critical buses and branches, which are prone to voltage instability. This study shows that the voltage stability margin and reactive power margin of the Karnali province power grid are low and decrease with increasing load demand. Small signal stability analysis shows a poorly damped local mode with a damping ratio as low as 5.61% in the increased load scenario, while transient stability shows a narrow critical clearing time, approximately 0.34 seconds in the decreased load condition. Frequency stability was within operational limits, showing robustness under disturbances.